Advances in Social Computing and Multiagent Systems 6th International Workshop on Collaborative Agents Research and Development, CARE 2015 and Second International Workshop on Multiagent Foundations of Social Computing, MFSC 2015, Istanbul, Turkey, May 4, 2015, Revised Selected Papers - Koch, Fernando; Guttmann, Christian; Busquets, Didac (Communications in Computer and Information Science,, 2015)
This book constitutes thoroughly revised, selected papers of the proceedings of the 6th International Workshop on Collaborative Agents Research and Development, CARE 2015 and the Second International Workshop on Multi-agent Foundations of Social Computing, MFSC 2015, held in Istanbul, Turkey, on May 4, 2015. Both Workshops were held in conjunction with AAMAS 2015. The 5 revised full papers of CARE and the 7 full papers of MFSC presented were carefully selected from 14 CARE and 10 MFSC submissions. Both workshop address issues in relevant areas of social computing such as smart societies, social applications, urban intelligence, intelligent mobile services, models of teamwork and collaboration.